Pelatihan Administrasi Digital Untuk Antisipasi Kegiatan Sekolah di Masa Pandemi Covid 19 - Harry Witriyono; Sandhy Fernandez; Dori Mabrori (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2021)
School activities during the Covid-19 pandemic forced teachers and students to carry out school activities in the form of learning at home. SD Negeri 05 Bengkulu Tengah uses the home learning method by requiring parents to come to school to collect and submit their children's learning documents. To anticipate this important school administration activity, digital administration training was held for schools so that these activities continued well even during the pandemic. The results of this administrative training are the creation of a school website, school profile videos, knowledge of K13 education report management through the Microsoft Excel application and the use of several online learning applications available on the internet network.